ANALISIS TINGKAT PENDAPATAN PEDAGANG CANANG DI PASAR BADUNG - Rustariyuni, Surya Dewi (Semarang State University, 2011)
This studyanalyzes thecharacteristic of âcanangâsellers, their economicactivities, their revenues, the factors which influencethem to chooseBadung Market for selling their products and theircontributions in their household economy. As a matter of fact,all of Hindu ismpeoplein Bali use canang everyday for conductingall ceremonies, but only few people whomake canang. It has occured foryears. The method used for analizing the data isdescriptive analysis. The result shows thatthe canang sellersare mostlyfrom Bali. They are dominated by married women atthe age of 15 up to 35 years old. Then, theireducational backgroundaresenior high schools. They start selling early in the morning and stop their activities in the evening.Finally, usually the sellers get much money when there is a big ceremony.Penelitian ini menganalisis karakteristik penjual